2014
DOI: 10.1002/jhm.2259
|View full text |Cite
|
Sign up to set email alerts
|

Development, implementation, and impact of an automated early warning and response system for sepsis

Abstract: Background Early recognition and timely intervention significantly reduce sepsis-related mortality. Objective Describe the development, implementation and impact of an Early Warning and Response System (EWRS) for Sepsis. Design After tool derivation and validation, a pre/post study with multivariable adjustment measured impact. Setting Urban academic healthcare system Patients Adult non-ICU patients admitted to acute inpatient units from: 10/01–10/31/2011 for tool derivation, 06/06–07/05/2012 for tool … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
140
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 158 publications
(146 citation statements)
references
References 17 publications
2
140
1
2
Order By: Relevance
“…The results showed that the total average cost was US$ 9,632.00 (R$ 21,566.00) per patient, www.ee.usp.br/reeusp Sepsis in a university hospital: a prospective study for the cost analysis of patients' hospitalization and the average daily rate cost was significantly higher for non-survivors (11) . The presented data warn the institutions about the need for investment in professional training for the early diagnosis and implementation of treatment at the appropriate time, in order to be more effective and contribute with patients' recovery, reducing the misdirection of investments that culminate in death (20) . The creation of a team for research and control of sepsis using management protocols for early diagnosis and appropriate treatment has proven an effective strategy to improve health indicators, such as reducing the chances of evolving to death by 30%, and reduction in days of hospital stay, which may reflect in reduction of hospital costs (20) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the total average cost was US$ 9,632.00 (R$ 21,566.00) per patient, www.ee.usp.br/reeusp Sepsis in a university hospital: a prospective study for the cost analysis of patients' hospitalization and the average daily rate cost was significantly higher for non-survivors (11) . The presented data warn the institutions about the need for investment in professional training for the early diagnosis and implementation of treatment at the appropriate time, in order to be more effective and contribute with patients' recovery, reducing the misdirection of investments that culminate in death (20) . The creation of a team for research and control of sepsis using management protocols for early diagnosis and appropriate treatment has proven an effective strategy to improve health indicators, such as reducing the chances of evolving to death by 30%, and reduction in days of hospital stay, which may reflect in reduction of hospital costs (20) .…”
Section: Discussionmentioning
confidence: 99%
“…The presented data warn the institutions about the need for investment in professional training for the early diagnosis and implementation of treatment at the appropriate time, in order to be more effective and contribute with patients' recovery, reducing the misdirection of investments that culminate in death (20) . The creation of a team for research and control of sepsis using management protocols for early diagnosis and appropriate treatment has proven an effective strategy to improve health indicators, such as reducing the chances of evolving to death by 30%, and reduction in days of hospital stay, which may reflect in reduction of hospital costs (20) . Note the limitation of this study having been performed in a teaching hospital, where many factors influence costs in comparison to other health institutions.…”
Section: Discussionmentioning
confidence: 99%
“…AeSAS employs two or more SIRS criteria as alert threshold (67)(68)(69)(70). Other studies use additional threshold such as SBP (71), and a lactic acid concentration >2 mmol/L (72,73). Two studies employed recursive partitioning tree analysis involving a variety of variables such as shock index, mean arterial blood pressure, international normalized ratio (INR), white blood cell (WBC) count, absolute neutrophil count, bilirubin, albumin, hemoglobin and sodium (74,75).…”
Section: Biomarkers and Screening Tools For Early Recognition Of Sepsismentioning
confidence: 99%
“…Tools that reliably detect early community-acquired sepsis are warranted and are the topic of intensive research. Meanwhile, there are studies focusing on early recognition of sepsis in hospitalized patients (110)(111)(112). As mentioned before, this patient population may be identified more easily and thus become more amenable for straightforward EGDT.…”
Section: The Importance Of Early Recognition Of Sepsismentioning
confidence: 99%